METHODS OF IMPROVEMENT AND ACTUAL PROBLEMS OF MODERN ECOLOGY IN UZBEKISTAN - Madrakhimova Z. N.; Jumaboyeva S. J.; Ismatova M. N. (European Science Publishing, 2024)
This article examines environmental problems in different regions of Uzbekistan and their solutions
Keywords: Ecology, Uzbekistan, population, environment, pollution, radiation, drinking water.